Assessing Impacts of Value Chain Development on Poverty : A Case-Study Companion to the 5Capitals Tool - Sheck, Ree (2013)
Over the past decade, many governmental, private or donor-funded programs have adopted value chain development (VCD) to address goals related to poverty reduction and economic development. Underlying the design of these programs is the assumption that smallholders will climb out of poverty when they organize into rural enterprises, when these enterprises link them to business partners committed to win-win relationships, and when the chain actors have access to the right mix of technical, business and financial services. However, despite considerable investments in VCD, we have a poor understanding of whether the underlying assumptions hold true. A major stumbling block to understanding has been the absence of sound metric systems to monitor progress and assess the impact of VCD initiatives. The 5Capitals tool, developed jointly by an alliance of research and development organizations, addresses this shortcoming by proposing an asset-based approach to assess the poverty impacts of VCD. The tool has been tested through 23 case studies carried out over two iterations in Asia, Africa, Latin America and North America. This chapter summarizes the process for development of the tool and the concepts that underpin its design, including the rationale for adopting an asset-based approach to pro-poor VCD. It introduces the five case studies selected for this volume to document the versatility of the tool for diverse value chains in various stages of development. It concludes with an overview of what the reader can expect in terms of insight from the case studies.